2005
DOI: 10.1001/jama.293.20.2487
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Suicide Ideation, Plans, Gestures, and Attempts in the United States, 1990-1992 to 2001-2003

Abstract: UICIDE IS ONE OF THE LEADING causes of death worldwide. As a result, the World Health Organization 1 and the US surgeon general 2 have highlighted the need for more comprehensive data on the occurrence of suicidal thoughts and attempts, according to the assumption that such data would be useful for planning national health care policy, as well as for evaluating efforts to reduce suicide and suicide-related behaviors. The latter are among the official national health objectives in the United States. 3 The assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
643
22
16

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 950 publications
(741 citation statements)
references
References 47 publications
60
643
22
16
Order By: Relevance
“…Comparing prevalence rates of suicidality across different studies may be more difficult than comparing rates of well defined mental disorders since the prevalence of suicidal ideation significantly varies across countries [37] and different cut off points for 'dichotomising' suicidality have been defined. A community survey of the general population in the USA [15] showed that in 2001-2003, the 12-month prevalence of suicidal ideation was 3.3% and the prevalence of suicidal plans 1% in the year before the interview, which is lower than the prevalence in our study. However, the magnitude of the difference is difficult to assess, since the studies used different time frames and in our study suicidality was assessed only within the past month.…”
Section: Comparison With Literaturecontrasting
confidence: 88%
“…Comparing prevalence rates of suicidality across different studies may be more difficult than comparing rates of well defined mental disorders since the prevalence of suicidal ideation significantly varies across countries [37] and different cut off points for 'dichotomising' suicidality have been defined. A community survey of the general population in the USA [15] showed that in 2001-2003, the 12-month prevalence of suicidal ideation was 3.3% and the prevalence of suicidal plans 1% in the year before the interview, which is lower than the prevalence in our study. However, the magnitude of the difference is difficult to assess, since the studies used different time frames and in our study suicidality was assessed only within the past month.…”
Section: Comparison With Literaturecontrasting
confidence: 88%
“…Throughout the twenty years assessed, rates of suicidal ideation (in the past two weeks) were 2 to 3 times higher in the current study (7.0-10.1%) than 12-month prevalence in the general population (2.8% [28]); however, they were somewhat lower than rates of suicidal ideation in individuals with spinal cord injury (15.4% [29]). Similarly, rates of suicide attempts in the past year reported at each follow-up assessment were at least two times higher in the present sample (1.1-1.7%) than in the general population (0.6% [25]) during years 1-15, but more similar at 20 years following injury (0.8%).…”
Section: Discussioncontrasting
confidence: 61%
“…The majority of individuals with suicidal ideation at year one were likely to meet criteria for MDD (87.6%) and almost one out of ten (8.1%) of them reported a suicide attempt in the first year after TBI. Relative to the general population, 38.9-41.9% of individuals who report suicidal ideation in the last 12 months meet criteria for MDD in the past year [28], which is notably less than in the current sample. Further, 12-month suicide attempt rates among individuals with suicidal ideation are 7.3-9.7% [28], which is comparable to the proportion of current ideators in the present sample who report a suicide attempt in the first year after injury.…”
Section: Suicidal Behaviour Following Tbi 14contrasting
confidence: 67%
“…Such findings are highly consistent with other large clinical studies reporting comorbid lifetime anxiety disorders at rates of 42% to 47.5% (23,25,33) and comorbid lifetime substance use disorders at rates of 40% to 43.7% (22,23,25). Finally, 39% of our patients reported a history of suicide attempts, which is slightly higher than the 31.8% found in the National Comorbidity Survey samples (34) and the 30% and 35.7% reported by the SFBN and STEP-BD studies, respectively. Similarly, both the Department of Veterans Affairs cooperative study and the Bipolar Disorder Case Registry reported rates of lifetime suicide attempts up to 65% within populations of patients with high unemployment and homelessness (24,27).…”
Section: Discussioncontrasting
confidence: 65%